Excavations of Gorgippia and its Necropolis in 2012 and 2016 - Goroncharovskiy, Vladimir A.; Kashaev, Sergey V. (Hyperboreus, 2019)
A survey of the excavations in Gorgippia conducted in 2012 and 2016 by the expedition of the Institute for the History of Material Culture (IHMC) in 2012 and 2016.